A Hybrid Fault-Tolerant Control for Nonlinear Active Suspension Systems Subjected to Actuator Faults and Road Disturbances. (22nd January 2020) - Pang, Hui; Liu, Xue; Shang, Yuting; Yao, Rui
Abstract : This paper proposes a hybrid fault-tolerant control strategy for nonlinear active suspension subjected to actuator faults and road disturbances. First, an augmented closed-loop system model is established for the nonlinear active suspension system with the actuator faults and road disturbances. Then, based on this model, a hybrid fault-tolerant controller that consists of a nominal state-feedback controller and a robust H ∞ observer is proposed to stabilize the control plant under fault-free condition and further compensate for the suspension performance loss under the actuator fault condition. Finally, a half-vehicle active suspension example is exploited to demonstrate the effectiveness of the proposed hybrid fault-tolerant controller under various running conditions.